'SUPRANATIONALISM' IN QUESTION: BELIEFS, VALUES, AND THE SOCIALIZING POWER OF THE EUROPEAN COMMISSION REVISITED. (6th April 2016) - CONNOLLY, SARA; KASSIM, HUSSEIN
Abstract : Do international organizations affect the views of the people who work for them? Although increasingly sophisticated methods have been used to address this question, disagreement persists about whether the beliefs of staff are formed before they join, after they enter the institution, or are shaped by instrumental calculation. Drawing on an original dataset based on the first fully representative survey of the European Commission's workforce, this article breaks new ground by putting different definitions of 'supranationalism' to the test and by capturing multiple ways in which individuals may be affected by the experience of working for the organization. For the first time, it demonstrates that commitment to 'supranationalism' varies between Commission staff groupings, that the influences on belief vary with the measure of 'supranationalism' used, and that both post‐recruitment experience and pre‐recruitment roles play a part in shaping beliefs.